2022
DOI: 10.1002/adma.202201731
|View full text |Cite
|
Sign up to set email alerts
|

A Lysosome‐Activated Tetrahedral Nanobox for Encapsulated siRNA Delivery

Abstract: Tetrahedral framework nucleic acids (tFNAs) have attracted extensive attention as drug nanocarriers because of their excellent cellular uptake. However, for oligonucleotide cargos, tFNA mainly acts as a static delivery platform generated via sticky‐ended ligation. Here, inspired by the original stable space inside the tetrahedral scaffold, a dynamic lysosome‐activated tFNA nanobox is fabricated for completely encapsulating a short interfering RNA (siRNA) of interest. The closed tetrahedral structure endows car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
82
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 44 publications
0
82
0
Order By: Relevance
“…The current–voltage recording of 10 glass nanopores with a size of 30 nm demonstrated that their average rectification ratio of −1.0 V/+1.0 V was 2.7 ± 0.2, as is plotted in Figure S1, indicating the repeatable fabrication of identical nanopipettes. On the other hand, TDNs are programmable DNA nanostructures featuring good rigidity and stability and have been applied in increasing arenas. Since altering the base pairs of the side chain of TDN had no obvious effect on the formation and stability of its structure, , herein we incorporated one AChE aptamer into one side chain of the TDN, empowering the as-designed TDN-apt with the capacity of AChE recognition. According to the sequences of five used strands as shown in Figure S2 and Table S1, the edge of the TDN was calculated to be ca.…”
Section: Resultsmentioning
confidence: 99%
“…The current–voltage recording of 10 glass nanopores with a size of 30 nm demonstrated that their average rectification ratio of −1.0 V/+1.0 V was 2.7 ± 0.2, as is plotted in Figure S1, indicating the repeatable fabrication of identical nanopipettes. On the other hand, TDNs are programmable DNA nanostructures featuring good rigidity and stability and have been applied in increasing arenas. Since altering the base pairs of the side chain of TDN had no obvious effect on the formation and stability of its structure, , herein we incorporated one AChE aptamer into one side chain of the TDN, empowering the as-designed TDN-apt with the capacity of AChE recognition. According to the sequences of five used strands as shown in Figure S2 and Table S1, the edge of the TDN was calculated to be ca.…”
Section: Resultsmentioning
confidence: 99%
“…The immunostimulatory CpG was prolonged on the single-stranded DNA (ssDNA) and CpG-tFNA was fabricated according to the previous study. Concisely, four designed ss CpG-DNAs (Sangon, Shanghai, China) were dissolved in TM buffer and denatured at 95 °C for 5 min. The detailed sequence of each ss CpG-DNA is displayed in Table .…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, people have developed ways of using and treating NOX-D20. Li et al (2019) combined a framework of nucleic acid (FNA) ( Zhang et al, 2021b ; Zhang et al, 2021c ; Gao et al, 2022 ) in the form of a DNA origami nanostructure to improve the stability and targeting of NOX-D20 in vivo . They used bipyramidal FNA as a drug delivery platform to deliver NOX-D20 to treat cerebral ischemia-reperfusion injury and achieved good results.…”
Section: Antagonistic Aptamers Against Pro-inflammatory Mediators (Pl...mentioning
confidence: 99%